let x0 be Real; :: thesis: for f1, f2 being PartFunc of REAL,REAL st f1 is_differentiable_in x0 & f2 is_differentiable_in x0 holds
( f1 - f2 is_differentiable_in x0 & diff ((f1 - f2),x0) = (diff (f1,x0)) - (diff (f2,x0)) )

let f1, f2 be PartFunc of REAL,REAL; :: thesis: ( f1 is_differentiable_in x0 & f2 is_differentiable_in x0 implies ( f1 - f2 is_differentiable_in x0 & diff ((f1 - f2),x0) = (diff (f1,x0)) - (diff (f2,x0)) ) )
reconsider j = 1 as Element of REAL by XREAL_0:def 1;
assume that
A1: f1 is_differentiable_in x0 and
A2: f2 is_differentiable_in x0 ; :: thesis: ( f1 - f2 is_differentiable_in x0 & diff ((f1 - f2),x0) = (diff (f1,x0)) - (diff (f2,x0)) )
consider N1 being Neighbourhood of x0 such that
A3: N1 c= dom f1 and
A4: ex L being LinearFunc ex R being RestFunc st
for x being Real st x in N1 holds
(f1 . x) - (f1 . x0) = (L . (x - x0)) + (R . (x - x0)) by A1;
consider L1 being LinearFunc, R1 being RestFunc such that
A5: for x being Real st x in N1 holds
(f1 . x) - (f1 . x0) = (L1 . (x - x0)) + (R1 . (x - x0)) by A4;
consider N2 being Neighbourhood of x0 such that
A6: N2 c= dom f2 and
A7: ex L being LinearFunc ex R being RestFunc st
for x being Real st x in N2 holds
(f2 . x) - (f2 . x0) = (L . (x - x0)) + (R . (x - x0)) by A2;
consider L2 being LinearFunc, R2 being RestFunc such that
A8: for x being Real st x in N2 holds
(f2 . x) - (f2 . x0) = (L2 . (x - x0)) + (R2 . (x - x0)) by A7;
reconsider R = R1 - R2 as RestFunc by Th4;
reconsider L = L1 - L2 as LinearFunc by Th2;
A9: ( L1 is total & L2 is total ) by Def3;
consider N being Neighbourhood of x0 such that
A10: N c= N1 and
A11: N c= N2 by RCOMP_1:17;
A12: N c= dom f2 by ;
N c= dom f1 by ;
then N /\ N c= (dom f1) /\ (dom f2) by ;
then A13: N c= dom (f1 - f2) by VALUED_1:12;
A14: ( R1 is total & R2 is total ) by Def2;
A15: now :: thesis: for x being Real st x in N holds
((f1 - f2) . x) - ((f1 - f2) . x0) = (L . (x - x0)) + (R . (x - x0))
let x be Real; :: thesis: ( x in N implies ((f1 - f2) . x) - ((f1 - f2) . x0) = (L . (x - x0)) + (R . (x - x0)) )
A16: x0 in N by RCOMP_1:16;
reconsider xx = x, xx0 = x0 as Element of REAL by XREAL_0:def 1;
assume A17: x in N ; :: thesis: ((f1 - f2) . x) - ((f1 - f2) . x0) = (L . (x - x0)) + (R . (x - x0))
hence ((f1 - f2) . x) - ((f1 - f2) . x0) = ((f1 . x) - (f2 . x)) - ((f1 - f2) . x0) by
.= ((f1 . x) - (f2 . x)) - ((f1 . x0) - (f2 . x0)) by
.= ((f1 . x) - (f1 . x0)) - ((f2 . x) - (f2 . x0))
.= ((L1 . (x - x0)) + (R1 . (x - x0))) - ((f2 . x) - (f2 . x0)) by A5, A10, A17
.= ((L1 . (x - x0)) + (R1 . (x - x0))) - ((L2 . (x - x0)) + (R2 . (x - x0))) by A8, A11, A17
.= ((L1 . (x - x0)) - (L2 . (x - x0))) + ((R1 . (x - x0)) - (R2 . (x - x0)))
.= (L . (xx - xx0)) + ((R1 . (xx - xx0)) - (R2 . (xx - xx0))) by
.= (L . (x - x0)) + (R . (x - x0)) by ;
:: thesis: verum
end;
hence f1 - f2 is_differentiable_in x0 by A13; :: thesis: diff ((f1 - f2),x0) = (diff (f1,x0)) - (diff (f2,x0))
hence diff ((f1 - f2),x0) = L . 1 by
.= (L1 . j) - (L2 . j) by
.= (diff (f1,x0)) - (L2 . 1) by A1, A3, A5, Def5
.= (diff (f1,x0)) - (diff (f2,x0)) by A2, A6, A8, Def5 ;
:: thesis: verum